Comparison of the Effects of Cognitive Behavioral Couple Therapy and Acceptance and Commitment Therapy on Intimacy and Marital Adjustment among Couples Applying for Divorce in Bushehr (Iran) - Seyed Esmaeil Mousavi Haghighi; Ali Pouladi Rishehri; Seyed Asghar Mousavi (Shiraz University of Medical Sciences, 2023)
Background: Family and marital abnormalities are among the risk factors of psychological trauma in family members and threaten the family system, which is the basis of any healthy society. The aim of the present study was to compare the effects of cognitive-behavioral couple therapy (CBCT) and acceptance and commitment therapy (ACT) on intimacy and marital adjustment among couples applying for divorce.Methods: This is a quasi-experimental study based on a pretestposttest design with a control group. The study population consisted of all married people applying for divorce in Bushehr city, (Iran) in 2021, 45 of whom were selected as the sample through convenience sampling and randomly and equally assigned to three groups (n= 15 per group). The first and second experimental groups received CBCT and ACT (twelve 90-minute sessions for each), respectively. The research instruments included Walker and Thompson's Intimacy Scale and Revised Dyadic Adjustment Scale. The data were statistically analyzed using univariate and multivariate analysis of covariance in SPSS-26.Results: The results showed a significant difference between the experimental groups and the control group in the post test scores of intimacy and marital adjustment (P<0.001). There was a significant difference between CBCT and ACT in improving marital adjustment (P=0.012), whereas these two interventions did not exhibit such a difference in improving intimacy.Conclusion: The study findings suggested that both CBCT and ACT can be used for improving the intimacy between the couples applying for divorce. However, CBCT is more recommended for improving the marital adjustment of such couples because it exhibited more effectiveness than ACT in this regard.